Metal supported ETS-10 molecular sieve catalyst, preparation method and application

By preparing metal-supported ETS-10 molecular sieve catalysts on ETS-10 zeolite support, the problems of low selectivity and high cost of existing catalysts are solved, and efficient glycerol conversion and glycerol carbonate selectivity are achieved, which is suitable for industrial applications.

CN119657217APending Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311217267.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing catalysts used for CO2 carbonylation glycerol reaction have low selectivity and low catalytic efficiency. The production cost of the new zeolite imidazole framework structure material catalyst is high, and it cannot achieve widespread industrial application.

Method used

A metal-supported ETS-10 molecular sieve catalyst was prepared by using multi-stage porous ETS-10 zeolite as a support, and a metal precursor was loaded by equal volume impregnation method to prepare a metal-supported ETS-10 molecular sieve catalyst for the reaction of glycerol and carbon dioxide to synthesize glycerol carbonate.

Benefits of technology

The glycerol conversion rate reached 34.5%, the selectivity of glycerol carbonate reached 86.3%, and the catalytic activity remained stable for 8 recycled times, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657217A_ABST
    Figure CN119657217A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-loaded ETS-10 molecular sieve catalyst, a preparation method and application, the metal-loaded ETS-10 molecular sieve catalyst takes hierarchical pore ETS-10 zeolite as a carrier, a metal precursor is loaded through an equivalent-volume impregnation method, and the mass ratio of the metal precursor to the ETS-10 zeolite molecular sieve is 5 wt%-15 wt%. The catalyst disclosed by the invention is simple in preparation method and low in cost, and when the catalyst is used for synthesizing glycerol carbonate through reaction of glycerol and carbon dioxide, the conversion rate of glycerol can reach 34.5%, and the selectivity of glycerol carbonate can reach 86.3%; and the catalytic activity of the catalyst can still be kept stable after the catalyst is recycled for 8 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesizing glycerol carbonate by carbonylation of glycerol with CO2, and in particular to a metal-supported ETS-10 molecular sieve catalyst, a preparation method and an application thereof. Background Art

[0002] Glycerol carbonate is a product of glycerol carbonylation. It is a low-toxic, easily degradable five-membered ring carbonate. It is widely used in battery electrolytes, curing agents for epoxy resins and other adhesives, organic synthesis intermediates and polymer monomers. The glycerol carbonate molecule contains a primary hydroxyl group and a five-membered ring carbonate ODO (2-oxo-l,3-dioxolane group) functional group, so it has a wide range of reactivity. At present, the research on the synthesis of glycerol carbonate mainly includes the following four synthetic routes: transesterification, urea alcoholysis, epoxide coupling and oxidative carbonylation. Among them, since glycerol and CO2 are both abundant and easily available resources, the atomic efficiency reaches 87%. Using CO2 to directly carbonize glycerol to synthesize glycerol carbonate is considered to be a very ideal reaction.

[0003] In the carbonylation reaction of CO2 and glycerol, since the C in CO2 exists in a +4 valence state, which is the highest valence state, it has high stability in both thermodynamics and kinetics. This also leads to the CO2 carbonylation glycerol reaction being subject to great thermodynamic restrictions (△G = 1.566 × 10-3), and the reaction needs to be carried out under high temperature and high pressure conditions. However, higher temperatures will cause dehydration within the glycerol molecule to form glycidol and intermolecular dehydration to form (mono)diglycerol and polyglycerol, greatly reducing the selectivity of the target product. Therefore, in order to improve the conversion rate of glycerol while taking into account industrial applications, it is necessary to develop highly active heterogeneous catalysts and introduce dehydrating agents into the reaction system to remove the water generated during the reaction to reduce the reaction energy barrier.

[0004] In recent years, various metal oxides, organometallic frameworks, and hydrotalcite catalysts have been used in the CO2 carbonylation of glycerol. The Shanxi Coal Chemistry Research Institute of the Chinese Academy of Sciences used oxides composed of transition metals and alkaline earth metals. Under the condition of 2,2-dimethoxypropane as a dehydrating agent, the glycerol conversion rate reached 30.8% and the yield of glycerol carbonate reached 13.0% (CN201310175799.3). Liu et al. prepared Ce1-xZrxO2 (0≤x≤0.2) solid solution by hydrothermal method, using dimethylformamide (DMF) as solvent and 2-cyanopyridine as dehydrating agent. The catalyst showed high catalytic activity (Biomass and bioenergy, 2018, 118: 74-83). Li et al. synthesized an anion-modified Zn-Al-La-M hydrotalcite catalyst by coprecipitation. When acetonitrile was used as a dehydrating agent, the glycerol conversion rate reached 35.5% and the selectivity of glycerol carbonate reached 45.07% (Journal of Molecular Catalysis A: Chemical, 2015, 402: 71-78). Hu et al. prepared a lanthanum-modified zeolite imidazole framework (La / ZIF-8). The modified ZIF-8 zeolite had a large specific surface area and its Lewis acidity and alkalinity also increased. The conversion rate of glycerol and the selectivity of glycerol carbonate reached 32% and 92%, respectively (Chemical Engineering Science, 2021, 235: 116451). Although this new zeolite imidazole framework structural material has obvious advantages in catalytic performance, its production cost is too high to be widely used in industry. Summary of the invention

[0005] In order to solve the technical problems that the existing catalysts used for CO2 carbonylation glycerol reaction have low target product selectivity and low catalytic efficiency, and the new zeolite imidazole skeleton structure material catalyst has high production cost and cannot be widely used in industry, the present invention provides a metal-loaded ETS-10 molecular sieve catalyst, a preparation method and its application in the synthesis of glycerol carbonate from glycerol and carbon dioxide.

[0006] The technical solution adopted by the present invention is:

[0007] A metal-loaded ETS-10 molecular sieve catalyst uses multi-level pore ETS-10 zeolite as a carrier and loads a metal precursor through an equal volume impregnation method, wherein the mass ratio of the metal precursor to the ETS-10 zeolite molecular sieve is 5wt% to 15wt%.

[0008] Furthermore, the metal precursor is at least one of zinc nitrate hexahydrate, copper nitrate hexahydrate, cerium nitrate hexahydrate, cobalt nitrate hexahydrate, zirconium nitrate pentahydrate, nickel nitrate hexahydrate or iron nitrate nonahydrate.

[0009] The preparation method of the above-mentioned metal-supported ETS-10 molecular sieve catalyst comprises the following steps:

[0010] (1) adding potassium fluoride solution and sodium hydroxide solution to water glass, stirring, then adding titanium trichloride, stirring evenly, then placing in a hydrothermal reactor and sealing, placing the sealed hydrothermal reactor in an oven for crystallization, and obtaining product A;

[0011] (2) taking out product A, washing, drying and calcining in sequence to obtain ETS-10 zeolite molecular sieve;

[0012] (3) adding the ETS-10 zeolite molecular sieve prepared in step (2) into the metal precursor solution, taking it out after immersion for a period of time, and calcining it to obtain a metal-supported ETS-10 molecular sieve catalyst.

[0013] Furthermore, in step (1), the molar ratio of the titanium source, potassium source, sodium source and water source is calculated according to SiO2: TiO2: K2O: Na2O: H2O: (6.0-8.0): 1.0: (1.5-2.5): (3.0-5.0): (150-220); wherein SiO2 refers to a silicon source, and the molar number of the silicon source is the molar number of silicon element in water glass; TiO2 refers to a titanium source, and the molar number of the titanium source is the molar number of titanium element in titanium trichloride; K2O refers to a potassium source, and the molar number of the potassium source is the molar number of the potassium element in potassium fluoride; Na2O refers to a sodium source, and the molar number of the sodium source is the sum of the molar numbers of the sodium element in the system derived from water glass and sodium hydroxide; H2O refers to a water source, and the molar number of the water source is the sum of the water contained in the system derived from water glass and other solutions.

[0014] Furthermore, in step (1), the crystallization temperature is 210-240° C. and the time is 48-80 hours.

[0015] Furthermore, in step (2), the drying temperature is 80-120° C., the drying time is 6-12 h, the calcination temperature is 300-600° C., and the calcination time is 4-8 h.

[0016] Furthermore, in step (3), the impregnation temperature is room temperature, the impregnation time is 6 to 12 hours, the calcination temperature is 300 to 500° C., and the calcination time is 4 to 8 hours.

[0017] The calcination temperature is 300-500°C, and the calcination time is 4-8h.

[0018] The above-mentioned metal-supported ETS-10 molecular sieve catalyst is used in the method for synthesizing glycerol carbonate from glycerol and carbon dioxide. Glycerol, the metal-supported ETS-10 molecular sieve catalyst and a dehydrating agent are added to a reactor, CO2 is introduced, and the reaction is carried out for 6 to 24 hours at a pressure of 3 to 5 MPa and a temperature of 160 to 180°C to obtain glycerol carbonate.

[0019] Furthermore, the dehydrating agent is at least one of acetonitrile, 2-cyanopyridine, calcium carbide, calcium oxide, calcium hydrogen phosphate, magnesium carbonate, N,N'-dicyclohexylcarbodiimide or 2,2-dimethoxypropane.

[0020] Furthermore, the mass ratio of the metal-supported ETS-10 molecular sieve catalyst to glycerol is 1:(16-30); and the molar ratio of the dehydrating agent to glycerol is (0.2-1):1.

[0021] The beneficial effects of the present invention are as follows: the metal-loaded ETS-10 molecular sieve catalyst prepared by the present invention uses a multi-level pore ETS-10 zeolite as a carrier to load a metal precursor, has a simple preparation method and low cost, and when used for the reaction of glycerol and carbon dioxide to synthesize glycerol carbonate, the glycerol conversion rate can reach 34.5%, and the glycerol carbonate selectivity can reach 86.3%; and the catalytic activity of the catalyst can remain stable after being recycled for 8 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the metal-supported ETS-10 molecular sieve catalyst prepared in Example 1.

[0023] Figure 2 This is a stability test chart of the metal-supported ETS-10 molecular sieve catalyst prepared in Example 1. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and a preferred implementation manner.

[0025] Unless otherwise specified in the following examples, all parts are parts by weight and all percentages are percentages by weight.

[0026] In the expression of the molar ratio of each material "SiO2: TiO2: K2O: Na2O: H2O" in the following embodiments and comparative examples, SiO2 refers to the silicon source, and the molar number of the silicon source is the molar number of the silicon element in the water glass; TiO2 refers to the titanium source, and the molar number of the titanium source is the molar number of the titanium element in the titanium trichloride; K2O refers to the potassium source, and the molar number of the potassium source is the molar number of the potassium element in the potassium fluoride; Na2O refers to the sodium source, and the molar number of the sodium source is the sum of the molar numbers of the sodium elements in the system derived from the water glass and the sodium hydroxide; H2O refers to the water source, and the molar number of the water source is the sum of the water contained in the system derived from the water glass and other solutions.

[0027] Example 1

[0028] Preparation method of metal-supported ETS-10 molecular sieve catalyst (5% Zn / ETS-10):

[0029] (1) Take 1.8 g potassium fluoride and dissolve it in 5 mL H2O to form solution A; take 1.45 g sodium hydroxide and dissolve it in 10 mL water to form solution B; add solution B dropwise into 9.2 mL water glass, the molar number of water glass is 3.4, and the SiO2 concentration is 5.9 mol / L; after stirring for 10 min, add 5.9 g TiCl3 dropwise; after stirring for 60 min, add solution A dropwise; after stirring for 2 h, put it into a hydrothermal reactor, seal it, and crystallize it in an oven at 230°C for 72 h; the molar ratio of each material in the system (SiO2:TiO2:K2O:Na2O:H2O) is 6.0:1.0:2.0:4.0:160.

[0030] (2) The product was taken out, washed, dried at 110° C. for 12 h, and calcined at 450° C. for 6 h to obtain ETS-10 zeolite molecular sieve.

[0031] (3) Take 1 g of the above-mentioned ETS-10 zeolite sample as a catalyst carrier, and introduce zinc nitrate hexahydrate by an equal volume impregnation method at a rate of 5 wt.% of the carrier mass. The impregnated sample is placed in air at room temperature for 12 h, then placed in an oven at 110°C for drying, and finally calcined at 450°C for 4 h to obtain a metal-supported ETS-10 molecular sieve catalyst, recorded as 5% Zn / ETS-10.

[0032] The electron microscope image of the obtained catalyst 5% Zn / ETS-10 is shown in Figure 1 .

[0033] from Figure 1 It can be seen that the catalyst sample prepared in the present invention presents a structural crystal with a typical biconical truncated shape, and the stacked ETS-10 crystals have uniform sizes (4-6.5 μm) and slight surface defects.

[0034] Example 2

[0035] Preparation method of metal-supported ETS-10 molecular sieve catalyst (5% Cu / ETS-10):

[0036] The preparation method of the catalyst is basically the same as that of Example 1, except that:

[0037] In step (1), the molar ratio of each material in the system is SiO2:TiO2:K2O:Na2O:H2O is 7.0:1.0:2.0:4.0:160, the crystallization temperature is 210°C, and the time is 80h;

[0038] In step (2), the drying temperature is 80°C, the drying time is 6 hours, the calcination temperature is 300°C, and the calcination time is 4 hours;

[0039] In step (3), the precursor used for impregnation is copper nitrate hexahydrate, the standing time is 6 hours, the calcination temperature is 300° C., and the calcination time is 4 hours.

[0040] Example 3

[0041] Preparation method of metal-supported ETS-10 molecular sieve catalyst (5% Ce / ETS-10):

[0042] The preparation method of the catalyst is basically the same as that of Example 1, except that:

[0043] In step (1), the molar ratio of each material in the system is SiO2:TiO2:K2O:Na2O:H2O is 7.0:1.0:1.5:4.0:160, the crystallization temperature is 240°C, and the time is 48h;

[0044] In step (2), the drying temperature is 120°C, the drying time is 12h, the calcination temperature is 500°C, and the calcination time is 6h;

[0045] In step (3), the precursor used for impregnation is cerium nitrate hexahydrate, the standing time is 16 hours, the calcination temperature is 500° C., and the calcination time is 6 hours.

[0046] Example 4

[0047] Preparation method of metal-supported ETS-10 molecular sieve catalyst (5% Co / ETS-10):

[0048] The preparation method of the catalyst is basically the same as that of Example 1, except that:

[0049] In step (1), the molar ratio of each material in the system is SiO2:TiO2:K2O:Na2O:H2O is 7.0:1.0:2.5:4.0:160, the crystallization temperature is 230°C, and the time is 80h;

[0050] In step (2), the drying temperature is 110°C, the drying time is 6 hours, the calcination temperature is 450°C, and the calcination time is 8 hours;

[0051] In step (3), the precursor used for impregnation is cobalt nitrate hexahydrate, the standing time is 24 hours, the calcination temperature is 450° C., and the calcination time is 8 hours.

[0052] Example 5

[0053] Preparation method of metal-supported ETS-10 molecular sieve catalyst (15% Zn / ETS-10):

[0054] The preparation method of the catalyst is basically the same as that of Example 1, except that:

[0055] The loading amount of the precursor zinc nitrate hexahydrate used for impregnation was 15 wt.% of the support.

[0056] Application Example 1

[0057] 0.25 g of the 5% Zn / ETS-10 catalyst powder obtained in Example 1 and 4 g of glycerol were added to a 200 mL high-pressure reactor, and then 5 mL of acetonitrile was added as a dehydrating agent, and 1 mL of tetraethylene glycol was added as an internal standard; CO2 was repeatedly introduced three times to remove excess air in the reactor, and 4 MPa of CO2 was introduced to carry out the carbonate glyceride synthesis reaction. The reaction conditions were: reaction temperature 160°C, reaction pressure 4.0 MPa, and reaction time 12 h.

[0058] After the reaction was completed, the pressure was released, the product was diluted with ethanol, and the product was quantitatively analyzed using gas chromatography. The analysis results are shown in Table 1. As can be seen from Table 1, the glycerol conversion rate was 23.1%, and the selectivity of glycerol carbonate was 37.4%.

[0059] Application Example 2

[0060] The catalyst in Application Example 1 was replaced by the catalyst 5% Cu / ETS-10 in Example 2, and the glycerol carbonate synthesis reaction was carried out under the same reaction conditions. The measured glycerol conversion rate was 27.1%, and the selectivity of glycerol carbonate was 26.6%.

[0061] Application Example 3

[0062] The catalyst in Application Example 1 was replaced by the catalyst 5% Ce / ETS-10 in Example 3, and the glycerol carbonate synthesis reaction was carried out under the same reaction conditions. The measured glycerol conversion rate was 24.0%, and the selectivity of glycerol carbonate was 25.5%.

[0063] Application Example 4

[0064] The catalyst in Application Example 1 was replaced by the catalyst 5% Co / ETS-10 in Example 4, and the glycerol carbonate synthesis reaction was carried out under the same reaction conditions. The measured glycerol conversion rate was 27.9%, and the selectivity of glycerol carbonate was 27.4%.

[0065] Application Example 5

[0066] The catalyst in Application Example 1 was replaced by the catalyst 15% Zn / ETS-10 in Example 5, and the glycerol carbonate synthesis reaction was carried out under the same reaction conditions. The measured glycerol conversion rate was 23.5%, and the selectivity of glycerol carbonate was 37.8%.

[0067] Application Example 6

[0068] The same method as in Application Example 1 was used, except that the reaction temperature was 170° C. The conversion rate of glycerol was measured to be 38.7%, and the selectivity of glycerol carbonate was 48.9%.

[0069] Application Example 7

[0070] The same method as in Application Example 1 was used, except that the reaction temperature was 180° C. The conversion rate of glycerol was measured to be 45.3%, and the selectivity of glycerol carbonate was 34.8%.

[0071] Application Example 8

[0072] The same method as in Application Example 1 was used, except that the reaction pressure was 3 MPa. The conversion rate of glycerol was measured to be 26.5%, and the selectivity of glycerol carbonate was 46.1%.

[0073] Application Example 9

[0074] The same method as in Application Example 1 was used, except that the reaction pressure was 5 MPa. The conversion rate of glycerol was measured to be 39.9%, and the selectivity of glycerol carbonate was 51.8%.

[0075] Application Example 10

[0076] The same method as in Application Example 1 was used, except that the reaction time was 6 h. The conversion rate of glycerol was measured to be 31.9%, and the selectivity of glycerol carbonate was 47.4%.

[0077] Application Example 11

[0078] The same method as in Application Example 1 was used, except that the reaction time was 24 h. The conversion rate of glycerol was measured to be 57.7%, and the selectivity of glycerol carbonate was 42.9%.

[0079] Application Example 12

[0080] The same method as in Application Example 1 was used, except that the catalyst prepared in Example 5 was used. The conversion rate of glycerol was measured to be 39.6%, and the selectivity of glycerol carbonate was 52.3%.

[0081] Application Example 13

[0082] The same method as in Application Example 1 was used, except that the mass ratio of catalyst to glycerol was 1:30, i.e., 0.4 g of catalyst was added. The conversion rate of glycerol was measured to be 41.7%, and the selectivity of glycerol carbonate was 53.1%.

[0083] Application Example 14

[0084] The same method as in Application Example 1 was used, except that the dehydrating agent was 2.78 g of CaC2. The conversion rate of glycerol was measured to be 33.4%, and the selectivity of glycerol carbonate was 80.4%.

[0085] Application Example 15

[0086] The same method as in Application Example 1 was used, except that the dehydrating agent was 2.4 g CaO. The conversion rate of glycerol was measured to be 29.4%, and the selectivity of glycerol carbonate was 80.2%.

[0087] Application Example 16

[0088] The same method as in Application Example 1 was used, except that the dehydrating agent was 4.5 g of 2-cyanopyridine. The conversion rate of glycerol was measured to be 88.3%, and the selectivity of glycerol carbonate was 43.6%.

[0089] Application Example 17

[0090] The same method as in Application Example 1 was used, except that the dehydrating agent was 5.9 g of calcium hydrogen phosphate. The conversion rate of glycerol was measured to be 87.4%, and the selectivity of glycerol carbonate was 23.32%.

[0091] Application Example 18

[0092] The same method as in Application Example 1 was used, except that the dehydrating agent was 3.65 g of magnesium carbonate. The conversion rate of glycerol was measured to be 34.5%, and the selectivity of glycerol carbonate was 86.3%.

[0093] Application Example 19

[0094] The same method as in Application Example 1 was used, except that the dehydrating agent was 1.6 g of N,N'-dicyclohexylcarbodiimide. The conversion rate of glycerol was measured to be 88.7%, and the selectivity of glycerol carbonate was 24.3%.

[0095] Application Example 20

[0096] The same method as in Application Example 1 was used, except that the dehydrating agent was 1.2 g 2,2-dimethoxypropane, and the catalyst was recycled 8 times. The cycle test data is shown in Figure 2 .

[0097] Comparative Example 1

[0098] (1) Microporous SAPO-56 zeolite molecular sieve was synthesized under hydrothermal conditions with a molar material ratio of Al2O3:H2O:P2O5:SiO2:TMHD=0.8:60:1.0:1.0:2.0.

[0099] First, 3g of pseudo-boehmite was dissolved in 19.5mL of deionized water. After continuous stirring, 3.9mL of 85wt% phosphoric acid solution was added to the resulting solution. Stirring was continued for 30 minutes, and 1.55g of gas phase silica gel was added to the resulting solution. Subsequently, 12mL of N,N,N',N'-tetramethyl-1,6-hexanediamine was added and stirred for 24 hours. Crystallize at 210°C for 48 hours, filter the resulting product, wash it to pH≈7, dry it at 105°C for 12 hours, and then calcine it at 560°C in a muffle furnace for 6 hours to finally obtain SAPO-56 zeolite molecular sieve.

[0100] (2) 1 g of the above-mentioned SAPO-56 zeolite sample was taken as a catalyst carrier, and zinc nitrate hexahydrate was introduced by an equal volume impregnation method at a rate of 5 wt.% of the carrier mass. The impregnated sample was placed in air and dried at room temperature for 12 hours, then placed in an oven at 110°C and finally calcined at 560°C for 6 hours to obtain a catalyst 5% Zn / SAPO-56.

[0101] Application Comparative Example 1

[0102] The same method as in Example 1 was used, except that the catalyst 5% Zn / ETS-10 in Example 1 was replaced by the catalyst 5% Zn / SAPO-56 in Comparative Example 1. The conversion rate of glycerol was measured to be 28.6%, and the selectivity of glycerol carbonate was 22.1%.

[0103] Comparative Example 2

[0104] (1) Microporous LSX zeolite molecular sieve was synthesized under hydrothermal conditions with a molar material ratio of Al2O3:H2O:Na2O:SiO2=1:122.0:6.25:2.2. First, 2.5 g of sodium aluminate was dissolved in 20 mL of deionized water. After continuous stirring for 10 min, 6.8 g of NaCl was added to the resulting solution, which was then further stirred for 10 min. Subsequently, a mixture consisting of 5.7 mL of water glass solution (SiO2 / Na2O molar ratio: 3.3, density: 1.38 g / cm3) and 8.5 mL of deionized water was added and stirred for 30 min. Crystallization was performed at 100 °C for 6.0 h. The product was filtered, washed to pH≈7, dried at 105 °C for 12 h, and then calcined at 550 °C in a muffle furnace for 4 h to finally obtain LSX zeolite molecular sieve.

[0105] (2) 1 g of the above LSX zeolite molecular sieve sample was used as a catalyst carrier, and zinc nitrate hexahydrate was introduced by an equal volume impregnation method at 5 wt.% of the carrier mass. The impregnated sample was placed in air and dried at room temperature for 12 hours, then placed in an oven at 110°C and finally calcined at 400°C for 6 hours to obtain a catalyst 5% Zn / LSX.

[0106] Application Comparative Example 2

[0107] The same method as in Example 1 was used, except that the catalyst 5% Zn / ETS-10 in Example 1 was replaced by the catalyst 5% Zn / LSX in Comparative Example 2. The conversion rate of glycerol was measured to be 33.4%, and the selectivity of glycerol carbonate was 27.5%.

[0108] Comparative Example 3

[0109] 1g of commercial ZSM-5 zeolite sample was used as a catalyst carrier, and zinc nitrate hexahydrate was introduced by an equal volume impregnation method at 5wt.% of the carrier mass. The impregnated sample was placed in air and dried at room temperature for 12 hours, then placed in an oven at 110°C and finally calcined at 400°C for 6 hours to obtain a catalyst 5% Zn / ZSM-5.

[0110] Application Comparative Example 3

[0111] The same method as in Application Example 1 was used, except that the catalyst 5% Zn / ETS-10 in Example 1 was replaced by the catalyst 5% Zn / ZSM-5 in Comparative Example 32. The conversion rate of glycerol was measured to be 35.6%, and the selectivity of glycerol carbonate was 18.0%.

[0112] Comparative Example 4

[0113] 1g of commercial X zeolite sample was used as a catalyst carrier, and zinc nitrate hexahydrate was introduced by an equal volume impregnation method at 5wt.% of the carrier mass. The impregnated sample was placed in air and dried at room temperature for 12 hours, then placed in an oven at 110°C and finally calcined at 400°C for 6 hours to obtain a catalyst 5% Zn / X Zeolite.

[0114] Application Comparative Example 4

[0115] The same method as in Application Example 1 was used, except that the catalyst 5% Zn / ETS-10 in Example 1 was replaced by the catalyst 5% Zn / X Zeolite in Comparative Example 32. The conversion of glycerol was measured to be 10.3% and the selectivity of glycerol carbonate was 6.2%.

[0116] Table 1 Reaction results of application examples 1-12

[0117]

[0118]

[0119] It can be seen from Table 1 above that at different crystallization temperatures, crystallization times, and calcination temperatures, catalysts loaded with different metals all have good catalytic performance (Application Examples 1 to 5). Compared with the catalyst prepared in the comparative example, the metal-loaded ETS-10 molecular sieve catalyst prepared by the present invention has a glycerol conversion rate of 57.7% and a selectivity of glycerol carbonate of 42.9% (Application Example 11) under the same reaction conditions, i.e., the same dehydrating agent, the same active component content, the same reaction temperature, reaction pressure, and reaction time. The glycerol conversion rate of the comparative example can only reach 35.6% at most (Application Comparative Example 3), and the selectivity of glycerol carbonate can only reach 27.5% at most (Application Comparative Example 2). The catalyst prepared by the present invention is significantly better than the prior art. And when the catalyst of the present invention is used in conjunction with a 2-cyanopyridine dehydrating agent (Application Example 16), the glycerol conversion rate can reach 88.3%, and the selectivity of glycerol carbonate can reach 43.6%. When the catalyst of the present invention is combined with three solid dehydrating agents, CaC2, CaO and magnesium carbonate (Application Examples 14, 15 and 18), the selectivity of glycerol carbonate can reach more than 80%.

[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications are also within the protection scope of the present invention.

Claims

1. A metal-supported ETS-10 molecular sieve catalyst, characterized in that: The multi-level pore ETS-10 zeolite is used as a carrier, and the metal precursor is loaded by an equal volume impregnation method. The mass ratio of the metal precursor to the ETS-10 zeolite molecular sieve is 5wt% to 15wt%.

2. A metal-supported ETS-10 molecular sieve catalyst according to claim 1, characterized in that: The metal precursor is at least one of zinc nitrate hexahydrate, copper nitrate hexahydrate, cerium nitrate hexahydrate, and cobalt nitrate hexahydrate.

3. A method for preparing a metal-supported ETS-10 molecular sieve catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) adding potassium fluoride solution and sodium hydroxide solution to water glass, stirring, then adding titanium trichloride, stirring evenly, then placing in a hydrothermal reactor and sealing, placing the sealed hydrothermal reactor in an oven for crystallization, and obtaining product A; (2) taking out product A, washing, drying and calcining in sequence to obtain ETS-10 zeolite molecular sieve; (3) adding the ETS-10 zeolite molecular sieve prepared in step (2) into the metal precursor solution, taking it out after immersion for a period of time, and calcining it to obtain a metal-supported ETS-10 molecular sieve catalyst.

4. The method for preparing a metal-supported ETS-10 molecular sieve catalyst according to claim 3, characterized in that: In step (1), the molar ratio of the titanium source, potassium source, sodium source and water source is calculated according to SiO2: TiO2: K2O: Na2O: H2O: (6.0-8.0): 1.0: (1.5-2.5): (3.0-5.0): (150-220); Among them, SiO2 refers to the silicon source, and the molar number of the silicon source is the molar number of the silicon element in the water glass; TiO2 refers to the titanium source, and the molar number of the titanium source is the molar number of the titanium element in titanium trichloride; K2O refers to the potassium source, and the molar number of the potassium source is the molar number of the potassium element in potassium fluoride; Na2O refers to the sodium source, and the molar number of the sodium source is the sum of the molar numbers of the sodium elements in the system derived from the water glass and sodium hydroxide; H2O refers to the water source, and the molar number of the water source is the sum of the water contained in the system derived from the water glass and other solutions.

5. The method for preparing a metal-supported ETS-10 molecular sieve catalyst according to claim 3, characterized in that: In step (1), the crystallization temperature is 210-240° C. and the time is 48-80 hours.

6. The method for preparing a metal-supported ETS-10 molecular sieve catalyst according to claim 3, characterized in that: In step (2), the drying temperature is 80-120° C., the drying time is 8-12 hours, the calcination temperature is 300-600° C., and the calcination time is 4-8 hours.

7. The method for preparing a metal-supported ETS-10 molecular sieve catalyst according to claim 3, characterized in that: In step (3), the impregnation temperature is room temperature, the impregnation time is 6 to 12 hours, the calcination temperature is 300 to 500° C., and the calcination time is 4 to 8 hours.

8. The method for synthesizing glycerol carbonate using the metal-supported ETS-10 molecular sieve catalyst according to claim 1 or 2, characterized in that: Add glycerol, the metal-supported ETS-10 molecular sieve catalyst and a dehydrating agent into a reaction kettle, introduce CO2, and react for 6 to 24 hours at a pressure of 3 to 5 MPa and a temperature of 160 to 180° C. to obtain glycerol carbonate.

9. The method according to claim 8, characterized in that The dehydrating agent is at least one of acetonitrile, 2-cyanopyridine, calcium carbide, calcium oxide, calcium hydrogen phosphate, magnesium carbonate, N,N'-dicyclohexylcarbodiimide or 2,2-dimethoxypropane.

10. The method according to claim 8, characterized in that: The mass ratio of the metal-supported ETS-10 molecular sieve catalyst to glycerol is 1:(16-30); the molar ratio of the dehydrating agent to glycerol is (0.2-1):1.

Citation Information

Patent Citations

  • Catalyst for synthesizing glycerol carbonic, preparation method for catalyst and application of catalyst

    CN103252239A

  • Cu / ETS-10 supported SCR catalyst synthesis method

    CN103272636A

  • Method for producing glycerol carbonate by direct carbonation reaction of glycerol and co2 in

    IN202041028146A